Code Mixing and Japanese Grammatical Interference to Indonesian Speech in Social Media Content - Suyanti Natalia (Hasanuddin University, 2023)
The unique culture and Indonesian lifestyle is widely listened to and it studied along with the Indonesian language learning process which is attended by many learners from foreign speakers. These foreign speakers reintroduced the Indonesian language, culture and lifestyle to the general public through various social media such as Instagram and YouTube platform. This phenomenon through the process of introducing Indonesian language especially native Japanese speakers, it creates various forms as a result of language contact including code mixing and interference. This research used qualitative method and descriptive in nature and it used sociolinguistics approach. The results of this research are found the form of code mixing and interference that appear on YouTube and Instagram content from the content, namely speech which contains code mixing and interference. The data that appears the most in the code-mixing process is in the form of groups of words and the data on the interference that appears the most is grammar at the syntactic level, followed by interference at the morphological level. Factors that cause this interference are differences in the structure of sentence patterns, differences in the process of affixation, and the process of conjugation in verbs and adjectives. The form of code mixing and interference that appears is a process of speaking Indonesian which is influenced by the sentence pattern or sentence structure of the native language of the speaker.